2021
DOI: 10.3390/mi12101178
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Spontaneous Surface Modifications on Polycrystalline Cu Due to Electric Fields

Abstract: We present a credible mechanism of spontaneous field emitter formation in high electric field applications, such as Compact Linear Collider in CERN (The European Organization for Nuclear Research). Discovery of such phenomena opens new pathway to tame the highly destructive and performance limiting vacuum breakdown phenomena. Vacuum breakdowns in particle accelerators and other devices operating at high electric fields is a common problem in the operation of these devices. It has been proposed that the onset o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Previous MD studies in polycrystalline metals, including Cu, have demonstrated that thermally annealing for 250 ps at 0.3–0.5 of the melting temperature of the metal promotes structural relaxation of the grains without allowing excessive grain growth . To regulate the temperature, a Nosé–Hoover thermostat , was used with a time constant of 1 ps, in line with previous MD studies in polycrystalline Cu . In the case of the bicrystalline Cu undergoing uniaxial tension, following energy minimization, the system is annealed to 300 K at a heating rate of 1.5 K/ps.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous MD studies in polycrystalline metals, including Cu, have demonstrated that thermally annealing for 250 ps at 0.3–0.5 of the melting temperature of the metal promotes structural relaxation of the grains without allowing excessive grain growth . To regulate the temperature, a Nosé–Hoover thermostat , was used with a time constant of 1 ps, in line with previous MD studies in polycrystalline Cu . In the case of the bicrystalline Cu undergoing uniaxial tension, following energy minimization, the system is annealed to 300 K at a heating rate of 1.5 K/ps.…”
Section: Methodsmentioning
confidence: 97%
“… 63 To regulate the temperature, a Nosé–Hoover thermostat 64 , 65 was used with a time constant of 1 ps, in line with previous MD studies in polycrystalline Cu. 66 In the case of the bicrystalline Cu undergoing uniaxial tension, following energy minimization, the system is annealed to 300 K at a heating rate of 1.5 K/ps.…”
Section: Methodsmentioning
confidence: 99%